The load[ing] city: Navigating layers of accumulation, movement and access in Muizenberg, Cape Town - Holtman, Alexandra-Naledi (School of Architecture, Planning and Geomatics, 2024)
This body of research is motivated by the need to address issues of separation. Being located in Cape Town where the urban fabric is largely informed by foundational work of the apartheid government, this research project seeks to reveal the multi-layered threads of ongoing challenges that manifest in socio-spatial dynamics. As the history of inherited dislocation traces its roots to Dutch colonial occupation beginning at Cape Town's shore, the city's coastal edge has long been a conflicted interface. With the establishment of harbours along with urban growth, the coastline has accumulated layers of tourism attraction and intersecting economies of large-scale global Capitalism and self-initiated trade linking and yet differentiating each coastal area. The highly active nature of the tidal zone and the act of constant renewal by oceanic waves is similarly reflected in the social ecosystems of growing economy and development. Despite constant flux in smaller temporal changes, histories of colonial dominance over the ocean and Cape Town's inland waters remain as is evident in the continued economic exclusion within the CBD echoed along the southern edge, in Muizenberg. Prior to the naming of the area, Muizenberg was occupied by Khoi communities, particularly, the Gorinaiqua, navigating the lowland areas of Zandvlei and moving through the lower slopes of Muizenberg Mountain. The 1600's brought the occupation of Dutch settlers into the area, with Het Post Huys being a remaining architectural marker of military presence. British occupation in the 19th century further solidified colonial dominance, setting roots firmly in place for the establishment of Muizenberg as a seaside town. Apartheid rule further instituted the racialising of coastal edges, with Muizenberg being established as a whites-only beach. After its institutional end, the social edges of Muizenberg are opaque, with its train station easing accessibility and its nature as a dynamic hub of both economic growth and recreation, bringing groups from across the metropole and beyond. However, its edges on the map present starker contrast, with settlements including Capricorn, Seawinds and Lavender Hill along its eastern edge, showcasing an apartheid-inherited fabric of division. Despite it being an area where both mountain and terrestrial waters meet the sea, Muizenberg is a site of both potential social and ecological connection and economic growth alongside threats of ongoing exclusion and disruption by gentrification. With Muizenberg being a site of urban growth nestled between mountain and sea, it echoes the pondering of Cape Town's coastal edges and growing disconnection along social and ecological lines at the hands of global capitalism. Additionally, it highlights the nature of edge-navigation in a post-apartheid city; its hardening by both inherited infrastructure and ongoing economic exclusion along with its dissolving through self-initiated trade and auto-construction. This study seeks to explore the dynamism of the coastal and urban edges of Muizenberg, uncovering the layers of socio-economic systems that have sculpted and continue to mould its form and the broader context of False Bay. As temporal tides bring new material to the shore through repeated motion, layers of ongoing accumulation are sought to be understood from within the context and with the load, a future imagined of a fabric that supports existing hopes and the long-held desire for greater connection.